Rational design of indoleamine 2,3-dioxygenase 1 (IDO1) inhibitors featuring 1,2,3-triazole derivatives with enhanced anti-inflammatory and analgesic efficacy - Liu, Qingying; Hou, Xixi; Wang, Yueliang; Tian, Mingyue; He, Baoyu; Guo, Jingjing; Yang, Jianxue (Frontiers in Pharmacology, 2025)
This study applied a target-based drug design approach focused on the IDO1 enzyme, which features a heme active site. By introducing a 1,2,3-triazole moiety capable of coordinating with the ferrous ion in heme, a series of 2H-benzo[b][1,4]oxazin-3(4H)-one derivatives were designed. Enzyme assays demonstrated that these compounds generally inhibited IDO1 activity, with Compound 14e showing the most potent effect, achieving an IC50 value of 3.63 μM. Molecular docking studies indicated that the 1,2,3-triazole ring in Compound 14e is positioned directly above the heme, forming a coordination bond with the ferrous ion. Additionally, it engages in π-π interactions with Phe263, while the amide group of the 2H-benzo[b][1,4]oxazin-3(4H)-one scaffold forms hydrogen bonds with Lys238. In vivo experiments in mice showed that Compound 14e significantly reduced CFA-induced upregulation of Iba1 in the spinal dorsal horn and alleviated mechanical hypersensitivity, thermal hyperalgesia, and spontaneous pain. Moreover, treatment with Compound 14e led to a significant reduction in the levels of pro-inflammatory cytokines TNF-α and IL-1β in CFA-treated mice. Importantly, Compound 14e demonstrated a favorable safety profile, with no observed toxicity in major organs, highlighting its potential as a promising anti-inflammatory and analgesic agent targeting IDO1.